(untitled) (Research, Society and Development, 2021)
This study aims to report the experience arising from the extension project “Gymnastics Workshop of the University Open to the Elderly”, conducted by students of the Physical Education Degree course at the State University of Bahia, Campus X. This is a qualitative descriptive study, carried out through content analysis method. The present investigation was carried out between March and December 2018. The classes of the project were subdivided into three moments, including warm up and stretching activities, main activities and cool down phase. Thirty elderly women participated in the gymnastics workshop activities, reporting that their participation in the extension project contributed to the improvement in quality of life in aspects related to physical, mental, social and emotional health. It was possible to verify the contentment of the participants when they rediscovered the pleasure of performing tasks that involved dances, games, dialogues and reflections. It was also observed that it is necessary to raise awareness among older men about the importance of physical activity for improving health. The experience obtained by the student monitors enabled greater proximity between teacher and students, strengthening the existing bonds, culminating in the present research. This intellectual colaboration reinforces the role of the Brazilian Public University to provide its students with teaching, research and extension activities in an articulated way, contributing to the formation of autonomous professionals who are able to intervene in the society.